REGIONAL CHARACTERISTICS OF HYDROLOGICAL FEATURES AND KARST PROCESSES IN THE NURATA DISTRICT - Kodirova, Mahfuza Makhmudovna (SCIENCE and SOCIETY, 2026)
This article presents a scientific and hydrological description of the main springs in the Nurota region and a comprehensive analysis of the role of the ‘Chashma’ hydrological feature within the regional ecosystem. The study sheds light on the Nurota mountain range, its complex karst systems and hydrological sources, as well as the hydraulic connectivity of its caves and springs.